Home Care Nurses' Experiences With Connected Continuous Glucose Monitoring Systems in Older Adults With Type 2 Diabetes: A Qualitative Study in France - Basma Berrag; Paul Quindroit (Journal of Gerontological Nursing, 2026)
Purpose: Connected continuous glucose monitoring (CGM) systems are increasingly used in managing older adults with diabetes. Although CGM systems offer clinical benefits, their implementation in home care remains challenging, especially for digitally excluded individuals. The current study sought to explore the experiences, perceptions, and support needs of French home care nurses in the use of connected CGM systems in the home-based care of older adults with type 2 diabetes. Method: A qualitative descriptive study was conducted with 11 home care nurses in northern France. Semi-structured interviews were analyzed using reflexive thematic analysis. Results: Four themes emerged: (1) A Promising Tool With Unresolved Practical Challenges , (2) Variable Digital Autonomy and the Role of Family Support , (3) The Evolving Role of the Home Care Nurse , and (4) Structural Gaps in Training and Support . Conclusion: CGM use among older adults relies heavily on nurses' ability to address technological and social barriers. Supporting their role is essential for equitable digital health adoption in aging care.